Usage of Fuzzy Logic and Machine Learning in Web Development - Čović, Zlatko (Bánki Közlemények, 2024)
This paper presents the possibility of using fuzzy logic and machine learning in web development with PHP programming language. Fuzzy logic and machine learning found their applications in various fields of web development. The Python programming language is one of the most popular for developing applications that utilize fuzzy logic and machine learning. When it comes to integrated web systems using some form of AI, it's common to see the AI module implemented using the Python programming language, while the rest of the system is written using other programming languages and technologies. API endpoints are created for data exchange among different languages within such systems. PHP, as a server-side programming language, is used on over 75% of websites, according to the W3Techs report. The work briefly describes the most popular libraries in the PHP programming language that are used for applying fuzzy logic and machine learning. Implementation requirements and basic features are listed.